Application Of Primum Remedium Principle in Corruption Criminal Acts In Decision (Number 46/Pid.Sus.TPK/2024/PN Mks) - Wirayudha, Budhi; Marsuni, Lauddin; Assaad, Andi Istiqlal (Faculty of Law, Universitas Muslim Indonesia, 2025)
This study aims to find out two things, namely the first to find out the legal considerations of the Panel of Judges in applying the primum remedium principle in decision Number 46 / Pid.Sus.TPK / 2024 / PN Mks and the second to find out the application of the Primum Remedium Principle in Corruption Crimes in Decision Case Number 46 / Pid.Sus.TPK / 2024 / PN Mks has met the legal objectives. The method in this study is to use normative legal research, the type of research is carried out by studying the laws and regulations in society related to the problems that the author is studying. The results of the study revealed that the legal considerations by the Panel of Judges in decision number 46 / Pid.SUS.TPK / 2024 / PN.Mks, have applied the primum remedium principle by imposing imprisonment and additional compensation in the form of compensation commensurate with state losses. Although this case meets the requirements for applying a restorative justice approach because the value of state losses is relatively small. Apart from this controversy, the Judge's considerations in the decision are in accordance with applicable legal regulations. ²The application of the primum remedium principle in Decision Number 46/Pid.Sus.TPK/2024/PN Mks has attempted to fulfill the three objectives of the law, namely the aspect of justice, the aspect of legal certainty, and the aspect of benefit. However, in the decision, the Panel of Judges prioritized legal certainty over justice and benefit. This can be seen from the decision to impose a 1-year prison sentence and a replacement fee of IDR 50,000,000, which shows the firmness in the application of the sentence. However, in terms of justice and benefit, there is still room for improvement, especially related to the impact of prevention and deterrent effects on future corruption crimes. The recommendation or suggestion given by the author is that the prosecutor's office in this decision needs to review the application of the SE Attorney General for Special Crimes Number B1113/F/Fd.1/05/2010 for corruption cases with small state losses, by considering the efficiency of case handling costs and the effectiveness of recovering state losses. For the Panel of Judges in handing down a verdict on corruption crimes, it is best to consider the balance between the three aspects of legal objectives (justice, legal certainty, and benefit) to achieve maximum deterrent effect.